Manual De Procedimiento Para La Información Contable Del Proyecto De Liv 7/24 (2022)
The law 1314 of 2009 and other regulations in accordance, support the globalization process and the international competitiveness, therefore, it must be contemplated and established rules and principles for the archival function, understanding that document management is a set of standards, techniques or practices that looks for a good handling or administration of the flow of documentation of a company, either through manual techniques or applying technologies.